“Empires of the Mind”? C.K. Ogden, Winston Churchill and Basic English - Garay, K. (Historical Papers / Communications historiques, 1988)
AbstractThis paper examines the relationship of Churchill's War Cabinet, and in particular of theprime minister himself to a simplified version of English devised by C.K. Ogden(1889-1957). “Basic English” was developed by Ogden during the late 1920s, the result ofan obsession with language and meaning which dated from his undergraduate days, andwhich was reinforced by the horrors of the First World War. “Basic” was but one ofmany attempts to devise a universal language made during the late nineteenth and earlytwentieth centuries.Following some minor successes during the 1930s, the real testing lime for Basicwas to come during the Second World War. Churchill seems to have been first attractedby the language's simple utility. He saw it as providing an easily learned medium ofcommunication between the polyglot wartime allies, but he soon began to glimpse itspotentially wider benefits for the post imperial era he was reluctantly being forced toenter. Nor was the possibility that Basic might foster a form of intellectual imperialismlost upon the scheme's enemies.While Basic English continues to be promoted and taught, the fall of Churchill'sgovernment in the summer of 1945 ensured that his grand design for Basic would neverbe realized.